Pathways to specialist community perinatal mental health services: a two-site longitudinal retrospective service evaluation - Nikolina Jovanović; Žan Lep; Jelena Janković; Aysegul Dirik; Anna Rees; Maev Conneely (NIHR Journals Library, 2024)
Background During pregnancy and the postpartum period, women's mental health can deteriorate quickly. Timely and easy access to services is critically important; however, little is known about the pathways women take to access services. Previous research has shown that women from ethnic minority groups in the United Kingdom experience more access issues compared to the White British women. Aim To describe pathways taken to specialist community perinatal mental health services and explore how they vary across services and ethnic groups. Methods This is a two-site, longitudinal retrospective service evaluation conducted in Birmingham and London during 6 months (1 July-31 December 2019). Electronic records of 228 women were accessed and data were extracted on help-seeking behaviour, referral process and the type of pathway (i.e. simple or complex). Data were collected using the adapted World Health Organization encounter form and analysed using uni- and multivariable analyses. Results The median time from the start of perinatal mental illness to contact with perinatal mental health services was 20 weeks. The majority of patients accessed perinatal mental health services through primary care (69%) and their pathway was simple, that is they saw one service before perinatal mental health services (63%). The simple pathway was used as a proxy for accessible services. In Birmingham, compared to London, more referrals came from secondary care, more women were experiencing current deterioration in mental health, and more women followed a complex pathway. Despite differences between ethnic groups regarding type of pathway and duration of patient journey, there was no evidence of difference when models controlled for confounders such as clinical presentation, general characteristics and location. The service's location was the strongest predictor of the type of pathway and duration of patient journey. Limitations The heterogeneity among categorised ethnic groups; data extracted from available electronic records and not validated with patient's own accounts of their pathways to care; unanalysed declined referrals; the study was conducted before the COVID-19 pandemic and pathways may be different in the post-COVID-19 period. Conclusion The study provides important insights into how patients find their way to community perinatal mental health services. It shows that there is a great degree of variability in the time taken to get into these services, and the pathway taken. This variation does not come from different needs of patients or different clinical presentations but rather from service-level factors. Future work The studied community perinatal mental health services in the United Kingdom operate with a significant degree of variability in the types and characteristics of patient pathways. Future research should explore these issues on the national and international levels. Additionally, future research should explore the reasons for the different pathways taken and the outcomes and risks associated with them. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 17/105/14. Plain language summary When women are pregnant or have just had a baby, their mental health can get worse quickly. It is very important for them to get help quickly and easily, but we do not know much about how women find and use perinatal mental health services during this time. Women from ethnic minority backgrounds in the United Kingdom often have more trouble accessing these services than White British women. In this study, we wanted to find out how women from different ethnic groups get to mental health services when they are pregnant or after having a baby. We looked at information from Birmingham and London, collected over 6 months in 2019. We studied the records of 228 women. Here is what we found: The middle time from when perinatal mental illness began until contact with perinatal mental health services was 20 weeks. Most women accessed services through primary care and their journey was straightforward. For example, after contacting their family doctor, they were next seen by the perinatal mental health service. When we looked at things like how unwell someone was, where they lived, and their background, we did not find any big differences between different ethnic groups in how they got to perinatal services. The place where the service was located was the most important factor in deciding how patients got there. Limitations First, we put together individuals from different ethnic groups to study them, but this might hide the differences between each group. Second, we only used information from patients' records, and we did not check with the patients themselves to make sure everything was right. Lastly, we did this study before the COVID-19 pandemic, so the way people get health care might have changed since then. Conclusion This study is the first to look at how women get to community mental health services for mothers. We found that it takes different amounts of time for women to reach these services, and they follow different paths. This difference does not seem to be because of what the patients need or how unwell they are, but because of how the services work. In the future, we should study what happens and what problems might come from these different ways of getting help.